Interference-aware iterative block decision feedback equalizer for single-carrier transmission - Souto, N. (2016)
The deployment of increasingly dense heterogeneous mobile networks can create high levels of interference among users that, combined with severely time-dispersive channels, can result in substantial performance degradation. To cope with both effects, in this paper, we propose an iterative block decision feedback equalizer (IBDFE) for single carrier (SC) transmissions that makes use of the correlation between the interference in the receiving antennas and minimizes the mean squared error (MSE) of the detected symbols. Our analytic and simulated performance results show that the proposed receiver can clearly outperform the conventional IBDFE and the linear interference rejection combining (IRC) detector in severely time-dispersive channels with strong cochannel interference.